A Comparison of the Caring Processes Used By Obstetric, Surgical, and Emergency Nurses When Caring for the Woman with a Fetal Loss. Issue 1 (June 2015) - Hutti, Marianne H.
<x xml:space="preserve">Abstract</x> Poster Presentation Objective To compare the caring processes used by obstetric, surgical, and emergency nurses in caring for women after fetal deaths. Design Qualitative study using focus group (FG) interviews. Setting Two large hospitals with Level‐III nurseries. Sample Four FGs were conducted involving 24 registered nurses currently working in labor and delivery, antepartum, surgery, postanesthesia, and emergency departments who had experience in caring for a patients with fetal losses and had been employed at least one year. Methods The open‐ended FG questions were carefully constructed based on the major concepts of Swanson's theory of caring, including knowing, doing for, being with, enabling, and maintaining belief. Interviews were audiotape recorded, transcribed verbatim, and deidentified. Transcripts were then uploaded into a software program for coding by research team members. Analysis was conducted using a continuously emergent process of data collection, data reduction, data display, and interpretation of data. Team members coded the transcripts that were then compared for agreement. Discrepancies in coding and theme identification were resolved through discussion. Results Nurses in all areas of specialty demonstrated all of Swanson's nurse caring processes but used them preferentially according to situational exigencies and level of rapport developed with the patient. All groups of nurses used maintaining belief with women experiencing fetal loss in smaller proportions than the other caring processes. Surgical and emergency nurses used doing for and knowing preferentially, while obstetric nurses used all of the caring processes except maintaining belief in approximately the same proportion. Surgical and emergency nurses reported a need for more education and mentoring regarding care after fetal loss, which may help them to be more comfortable in using the caring processes of being with and enabling. Conclusion/Implications for Nursing Practice Nurses try very hard to give the best care they can to women after fetal loss. Opportunities for nurses to share expertise across specialties on common problems could help increase collegiality and comfort with high intensity clinical situations.